The Influence of Value Added Tax (VAT) on Online Buying and Selling Transactions on Shopee in the Sumedang Community - Raharjo, Rezi Dwi Putriani; Raharjo, Reza Dwi Fitriani; Nurmayanti, Santi; Rosalinda, Rosalinda (SINTESA, 2024)
This research aims to analyze the influence of Value Added Tax (VAT) on online buying and selling transactions on the Shopee platform carried out by the people of Sumedang. With the development of technology and fast internet use, online transactions are increasing in Indonesia. Through a quantitative approach using survey methods and data collection using questionnaires, this research tests the hypothesis that there is an influence of VAT on online buying and selling transactions at Shopee. It is hoped that the research results will provide a deeper understanding of the impact of VAT on online transactions and contribute to the development of tax policy in e-commerce. In conclusion, this research is important for understanding the relationship between VAT and online transactions in today's digital era. This research aims to analyze the influence of Value Added Tax (VAT) on online buying and selling transactions on the Shopee platform carried out by the people of Sumedang. With the development of technology and fast internet use, online transactions are increasing in Indonesia. Through a quantitative approach using survey methods and data collection using questionnaires, this research tests the hypothesis that there is an influence of VAT on online buying and selling transactions at Shopee. It is hoped that the research results will provide a deeper understanding of the impact of VAT on online transactions and contribute to the development of tax policy in e-commerce. In conclusion, this research is important for understanding the relationship between VAT and online transactions in today's digital era